Trans–Pars Interarticularis Approach for Lumbar Interbody Fusion: An Efficient, Straightforward, and Minimally Invasive Surgery for Lumbar Spondylolisthesis and Stenosis - Liu, Zhao-Quan; Hsieh, Cheng-Ta; Chang, Chih-Ju (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Lumbar interbody fusion is a commonly applied surgical treatment for spondylolisthesis. For this procedure, various minimally invasive (MIS) approaches have been developed, including posterior lumbar interbody fusion, transforaminal lumbar interbody fusion (TLIF), oblique lumbar interbody fusion, and anterior lumbar interbody fusion. In this study, we characterized the features of an MIS trans–pars interarticularis lumbar interbody fusion (TPLIF) and compared its surgical outcomes with those of MIS-TLIF.This study included 89 and 44 patients who had undergone MIS-TPLIF and MIS-TLIF, respectively, between September 2016 and December 2022. The following clinical outcomes were analyzed: operative time, blood loss, and hospitalization duration.The average operative time, blood loss, and hospitalization duration for the MIS-TPLIF and MIS-TLIF groups were, respectively, 98.28 and 191.15 minutes, 41.97 and 101.85 mL, and 5.8 and 6.9 days.The MIS-TPLIF approach for lumbar spondylolisthesis or other degenerative diseases involves the use of the commonly available and cost-effective instrument Taylor retractor, thus enabling posterior lumbar interbody fusion to be performed with minimal invasion. This approach also confers the benefits of a short learning curve and an intuitive approach. Our results suggest that although MIS-TPLIF is noninferior to MIS-TLIF, it is easier to learn and perform than MIS-TLIF.
Keywords: posterior lumbar interbody fusion; trans–pars interarticularis lumbar interbody fusion; transforaminal lumbar interbody fusion; spondylolisthesis; minimally invasive spine surgery